Pro BizTalk 2009 - Dunphy, George (Expert's voice in BizTalk., 2009)
"A compendium of best practices and implementation wisdom, Pro BizTalk 2009 is based upon real feedback from BizTalk developers. BizTalk experts and authors share their experiences and expertise to teach you the art of creating a BizTalk solution using the right tools from the BizTalk 2009 toolbox"--Resource description page